1995
DOI: 10.1007/bf02208342
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble forms of T cell activation antigens CD27 and CD25 in systemic lupus erythematosus in relation with lymphocytes count and disease course

Abstract: SummarySystemic lupus erythematosus (SLE) patients are characterized by a low lymphocyte count, which is considered a specific disease marker and is related to disease activity. The membrane bound molecules CD25 and CD27 are expressed and released in a soluble CD25 (sCD25) and soluble CD27 (sCD27) form by activation of predominantly T cells. In previous studies it was claimed that sCD25 as well sCD27 might be used as parameters for activation of the immune system; a correlation between the sCD25 profile with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…This protein is expressed transiently by activated CD4 + T cells (30,(35)(36)(37). However, CD154 also can be cleaved from the cell surface of activated T cells, releasing an sCD154 of approximately [18][19][20]. This sCD154 can apparently form homotrimers that can induce B-cell activation or differentiation (33,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein is expressed transiently by activated CD4 + T cells (30,(35)(36)(37). However, CD154 also can be cleaved from the cell surface of activated T cells, releasing an sCD154 of approximately [18][19][20]. This sCD154 can apparently form homotrimers that can induce B-cell activation or differentiation (33,38).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, soluble proteins released from activated T cells may contribute to immune activation (20)(21)(22)(23). TNF-α, for example, is a protein that can exist as either a soluble molecule or a membrane-associated glycoprotein (24)(25)(26).…”
mentioning
confidence: 99%
“…The increase in sIL-2R levels was most pronounced with major flares, especially in nephritis [39,[42][43][44] and rises in sIL-2R levels preceded flares [40,41]. These results suggest that sIL-2R can be considered as a promising candidate biomarker of activity in patients with SLE, especially among those with kidney involvement.…”
Section: Cytokine and Cytokine Receptorsmentioning
confidence: 91%
“…Several studies demonstrated an increase of sIL-2R levels during flares and a decrease with treatment and clinical improvement [33,[39][40][41][42][43]. The increase in sIL-2R levels was most pronounced with major flares, especially in nephritis [39,[42][43][44] and rises in sIL-2R levels preceded flares [40,41].…”
Section: Cytokine and Cytokine Receptorsmentioning
confidence: 99%
“…In peripheral blood of systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) patients, hyper activation of T-cells has been found [9,10], and this activation was correlated with their clinical course [11,12]. Moreover, activated T-cells reportedly take important part in pathogenesis of SLE by coordinating production of autoantibody with B-cell [13] and in RA by leading to chronic inflammation in synovial joint [14].…”
Section: Introductionmentioning
confidence: 99%